Simultaneous speciation of chromate, molybdate and arsenate in lysimetric water from geotechnical composites installed in field lysimeters - Marija Djurić; Lucija Levstek; Primož Oprčkal; Ana Mladenovič; Alenka Mauko Pranjić; Janez Ščančar; Radmila Milačič (Scientific Reports, 2022)
Abstract Anion-exchange high performance liquid chromatography inductively coupled plasma mass spectrometry (HPLC-ICP-MS) was used for simultaneous speciation of chromate, molybdate and arsenate. The repeatability of measurement tested for multielemental standard solution of chromate, molybdate and arsenate (50 ng mL−1 of Cr, Mo and As, pH 12) was ± 0.9%, ± 4.9% and ± 4.1%, respectively. Limits of quantification (LOQs) were low (0.53 ng mL−1 for chromate and arsenate and 1.03 ng mL−1 for molybdate, expressed as elemental concentrations). A wide linear concentration range (from LOQs to 500 ng mL−1) was obtained. The performances of this method enabled simultaneous speciation analysis in samples of water from lysimeters, in which three geotechnical composites, made of recycled waste, were installed in parallel in compacted and uncompacted, 20 times less dense form. The release of toxic chemical species of elements into lysimetric waters from each composite was studied. The results revealed that the degree of compaction and the composition of composites both have a significant influence on leaching of chromate, molybdate and arsenate. The study proved that multielemental speciation analysis is fast and cost-effective method for investigations of environmental impacts of materials, made from recycled waste, and can be used in other similar applications.